PENGARUH PANDEMI COVID-19 TERHADAP TINGKAT KEMISKINAN DI JAWA TIMUR - Reynya Oktaviani Sena; I Made Suparta (CV. Denasya Smart Publisher, 2024)
This study aims to determine the influence of Covid-19 on the poverty rate in East Java Province from 2019-2022, which was carried out using a qualitative approach using descriptive data taken from BPS (Central Statistics Agency) East Java data per Regency/City from 2019-2022. The results of the research obtained that the influence of covid on the poverty level from the beginning before the covid occurred, namely in 2019, by looking at which areas have a high poverty rate and which areas have a low poverty rate.In 2020, during the Covid pandemic, we looked for data on which areas had increased poverty rates, and which areas had not increased poverty rates, in 2021 poverty after the pandemic was looking for data on which areas could reduce poverty rates, and which areas had not been able to reduce poverty rates, and in 2022 we were looking for data on which areas could reduce poverty rates, and which areas have not been able to reduce the poverty rate, and which areas have not been able to reduce the poverty rate, and what are the policies carried out by the government to reduce poverty due to the Covid-19 pandemic.